A systematic revision of the scale mite genus Pterygosoma Peters, 1849 (Acariformes: Pterygosomatidae) - Fajfer, Monika (Zootaxa, 2020)
A systematic revision of the scale mites of the genus Pterygosoma (Acariformes: Pterygosomatidae) associated with agamas (Reptilia: Agamidae) was carried out based on type-material and numerous samples collected all over the world. For the natural species groups established in Fajfer (2019) diagnoses are presented. All Pterygosoma species are re-diagnosed or redescribed with simultaneous re-examination of host-parasite associations. Several taxonomic changes are implemented in the course of re-examination of the type series: seven subspecies of the genus Pterygosoma are elevated to species rank (with their former stem species in parentheses): P. aculeatum Lawrence, 1936 (agamae), P. angolae Jack, 1962 (melanum), P. capensis Jack, 1962 (melanum), P. longipalpae Lawrence, 1936 (melanum), P. orbicularis Jack, 1962 (spinosa) and P. pseudorbicularis Jack, 1962 (bibronii), P. problematica Jack, 1962 (fimbriata); four species are synonymized: Pterygosoma expansum Bertrand, Finkelman and Paperna, 2000 is synonymized with P. adramitana Jack, 1961 and consequently P. gladiator Bertrand, Finkelman and Paperna, 2000 with P. neumanni (Berlese, 1910), P. rhipidostichata Bertrand, Finkelman and Paperna, 2000 with P. mutabilis Jack, 1961 and P. livingstonei Bertrand and Modry, 2004 with P. circularis Jack, 1962; new hosts and distribution records are given for Pterygosoma neumanni (Berlese, 1910), P. bibronii Jack, 1962, P. longipalpae Lawrence, 1936, P. gracilipalpis and P. sinaita Jack, 1961. The protonymphs of Pterygosoma engai Fajfer, 2013, P. indare Fajfer, 2013, P. longipalpae Lawrence, 1936, and the deutonymph of P. transvaalense Lawrence, 1936 are described for the first time. A revision of leg chaetotaxy models i.e. coxae-trochanters I−IV and tarsi I−IV proposed by Jack (1964) is conducted and new species groups for Pterygosoma species are proposed. A key to all Pterygosoma species is provided. A full list of Pterygosoma species with their corrected host associations and distribution data is compiled.